The cancer patient and medical dermo-pigmentation: psychological aspects. - Vachtsenovanos , Sofia; Rubino, Luca; Santi, Pierluigi; Friedman, Daniele; Battaglia, Claudio (Medicina Historica, 2023)
This work aims to assess breast cancer treatment's physical and psychological impact on patients undergoing it, particularly regarding emotional and social issues. The focus is on the extent to which reconstructive procedures can alleviate problems the operated patients are facing and on whether the completion of the reconstructive procedure, through the reconstruction, or restructuring of the nipple-areola complex through minimally invasive methods, such as tattooing, i.e. micropigmentation, is an important requirement in order for the patient to forget about the disease, or reduce the impact its memory brings.